Characterization of CVD diamond film and diamond-tip field emitter array for FED applications - Ju, Byeong Kwon; Kim, Seong-Jin; Lee, Yun Hi; Park, Beom Soo; Baik, Young-Joon; Lim, Sungkyoo; Oh, Myung Hwan (Proceedings of the IEEE International Vacuum Microelectronics Conference, IVMC, 1996)
Diamond-tip field emitter arrays and a flat diamond films were fabricated and characterized. The tip radius of 300 angstroms was obtained by using a silicon mold formed by orientation dependent etching (ODE). The fabricated diamond-tip array was identified as diamond from Raman spectroscopy. Emission current of 200 μA and threshold voltage of 600 V were obtained for the diamond-tip field emitter arrays from the current-voltage measurement. Emission current of 6 μA and threshold voltage of 800 V were obtained from the flat diamond film deposited under the same condition as diamond-tip field emitter arrays. The diamond-tip field emitter arrays were shown to have better electrical characteristics than the flat diamond films.